The Predictive Ability of Academic Self-Efficacy Domains of Mindfulness and Academic Fatigue among High Achieving Students - Melhem, Mohamed; Aljrah, Abdalnaser; Shraideh, Mohammed; Hayajneh, Waleed (Dirasat: Human and Social Sciences, 2023)
The study examined the predictive ability of academic self-efficacy domains of mindfulness and academic fatigue among high-achieving students and sought to identify differences in the different domains of academic fatigue among high-achieving students due to gender and grade level. The sample of the study consisted of (87) high-achieving students selected using a purposeful sampling method. To achieve the objectives of the study, Academic Self-Efficacy; Mindfulness, and Academic Fatigue scales were employed. The results of the study indicated that the persistence domain of the academic self-efficacy total construct was the only significant predictor of academic fatigue among high-achieving students. It was able to account for (11.6%) of the total variance in academic fatigue. The study also showed that there were no statistically significant differences in academic fatigue levels among high-achieving students due to gender, while significant differences were found due to grade level, in favor of 12th-grade students.